Self-Propagating Combustion Synthesis, Luminescent Properties and Photocatalytic Activities of Pure Ca12Al14O33: Tb3+(Sm3+) - Liu, Rong; Yan, Yongsheng; Ma, Changchang (Frontiers in Chemistry, 2018)
The dual-functional Ca12Al14O33: Tb3+ and Ca12Al14O33: Sm3+ materials were prepared by the Self-Propagating Combustion Synthesis (SPCS) technology. The structure, morphology and light absorption property were investigated by XRD, FT-IR, UV-Vis DRS and SEM etc. The doping of Tb3+ and Sm3+ ions had not changed cubic structure of Ca12Al14O33 but leaded to the slight lattice dilatation and the red-shifts of absorption peaks/edges. The excitation and emission spectra indicated that Ca12Al14O33: Tb3+ and Ca12Al14O33: Sm3+ are superior green and red luminescent materials, respectively, and it displayed the distinctly refined structure characteristics which had importantly reference value for the energy level investigation of Tb3+ and Sm3+ ions. Meanwhile, Ca12Al14O33: Tb3+ and Ca12Al14O33: Sm3+ also exhibited the improved photocatalytic degradation for removing dye MB compared with bare Ca12Al14O33.